(untitled) (Costos y Gestión, 2023)
Through the costing based on time spent per activity and cost allocation, time is used as an inductor of the activity, and under the premise that the practical capacity cannot be equal to the theoretical capacity, the present study is developed, with the objective of proposing a costing based on time spent per activity (TDABC), for a tomography service; through an inductive, descriptive, cross-sectional study, using observation and data analysis, the study was carried out in collaboration and coordination with the financial area and the staff of the tomography area. The results incorporate the analysis of procedures and sub-procedures, activities and comparisons, as well as the results of the costing through the TDABC, as is the case of a service in which 38 minutes are invested for processing and attention, according to the TDABC method, the cost of the service would be S/ 597.47.